Production and modifications of biochar to engineered materials and its application for environmental sustainability: a review - Ravindiran G.; Rajamanickam S.; Janardhan G.; Hayder G.; Alagumalai A.; Mahian O.; Lam S.S.; Sonne C. (Springer, 2025)
Biochar, a carbon-rich material produced from biomass waste through thermal conversion, holds great environmental promise. This article offers a comprehensive overview of the various feedstocks used in biochar production, the different types of thermal degradation processes, biochar characterization, properties, modifications to engineered materials, and their applications in the environment. The quality of biochar, including surface area, pore size and volume, and functional group formation, is significantly influenced by the specific conditions under which thermal conversion takes place. Each of the diverse processes employed to produce biochar yields a distinct set of properties in the final product. In recent years, biochar has gained widespread recognition and utilization in diverse fields such as wastewater treatment, carbon sequestration, reduction of greenhouse gas emissions, biogas production, catalysis in biofuel industries, construction, and soil enhancement. In summary, biochar is a promising environmental mitigation tool to achieve a sustainable environment. In addition to its benefits, the application of biochar presents several challenges, including the selection of feedstocks, methods of biochar production, modifications to biochar, the properties of biochar, and the specific applications of biochar. The current review summarizes factors that could lead to significant advancements in future applications. Graphical Abstract: (Figure presented.) ? The Author(s) 2024.